Effects of oriental medicine music therapy in an ovarian cancer patient with So-Eum-type constitution: a case report - Seung-Hyun Lee; Eunhye Song; Seul-Ki Kim (Integrative Medicine Research)
The cancer incidence in Korea has been increasing, although there is a serious lack of supportive care for the treatment and management of the rapidly increasing number of cancer patients, and there is an immense need for therapeutic interventions to support cancer patients. A 47-year-old So-Eum-type Korean female patient, who was diagnosed with ovarian cancer, had been receiving chemotherapies. She was experiencing pain due to swelling of her hands and feet, and under extreme stress due to hardships of life. During the patient's fourth chemotherapy treatment, she received oriental medicine music therapy twice per week for 2 weeks, for 1 hour each time (4 sessions in total). A self-administered questionnaire and the visual analog scale were used to assess and determine the level of negative and positive feelings. After receiving the oriental medicine music therapy, her negative and positive feelings as well as the visual analog scale score that reflects subjective health conditions have improved and stabilized. This case report suggests the potential of oriental medicine music therapy as a complementary and alternative medical treatment method to promote and enhance quality of life and health conditions of cancer patients in postsurgical care and chemotherapy treatment.